Signifikansi Proses Pencarian Makna terhadap Teks Agama: Menyibak Pemikiran Nasr Hamid Abu Zaid - Muzakki, Akhmad (el Harakah: Jurnal Budaya Islam, 2006)
Basically, according to Gadamer, words belong to and are based on the reality. Human beings look for the appropriate words to express the reality. Ontologically; human beings do not create language as a means of communication and thinking, but it was created more as the representation of reality while they articulated the language. Therefore, the meaning of words exists in the thought. According to Saksitri’s theory, a word is considered as sign related to signifiant (something signifying) and signifie (something signified). Signifiant explains the form or expression, and signifie explains the thought or meaning. The relation, brtween signifiant and signifie based on the social convention is called significance or maghza according to Nasr Hamid. On the other words, significance is an effort to give meaning to sign (language). According to linguists,such as Jacques Derrida, the last signifie is not"always recognized. For Derrida; meaning appears from the metaphor exchange, and meaning will change ,when the speakers change, or; as stated by Nasr Hamid, the meaning of religious texts are not determined when the texts appeared for the first time, but they are dynamic, relational, and moveable depending on the socio-cultural condition of the readers. Pada dasarnya, menurut Gadamer, kata - kata dimiliki dan didasarkan pada realitas. Manusia mencari kata-kata yang tepat untuk mengekspresikan realita. Secara onologis; Manusia tidak menciptakan bahasa sebagai sarana komunikasi dan pemikiran, namun diciptakan lebih sebagai representasi realitas saat mereka mengartikulasikan bahasa Oleh karena itu, makna kata ada dalam pemikiran. Menurut teori Saksitri, sebuah kata dianggap sebagai tanda yang terkait dengan signifiant (sesuatu yang menandakan) dan menandakan (sesuatu yang ditandai). Signifiant menjelaskan bentuk atau ungkapan, dan signifie menjelaskan pemikiran atau makna. Hubungannya, brtween signifiant dan signifie berdasarkan konvensi sosial disebut signifikansi atau maghza menurut Nasr Hamid. Dengan kata lain, signifikansi adalah sebuah usaha memberi arti tanda (bahasa). Menurut ahli bahasa, seperti Jacques Derrida, Tanda terakhir tidak "selalu dikenali, karena Derrida, yang berarti muncul dari pertukaran metafora, dan makna akan berubah, ketika pembicara berubah, atau, seperti yang dinyatakan oleh Nasr Hamid, makna teks agama tidak ditentukan saat teks muncul untuk Pertama kali, tapi dinamis, relasional, dan mudah bergerak tergantung kondisi sosio-kultural pembaca.